Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2166/wst.2022.419
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic discharge from a wastewater treatment plant: long term monitoring to compare two analytical techniques, LDIR and optical microscopy while also assessing the removal efficiency of a bubble curtain

Abstract: In this study we compare two parallel analytical methods while also testing a microplastics mitigation method. We assess the effectiveness of a bubble curtain to reduce microplastics in a wastewater treatment plant (WWTP)-effluent canal during the course of six months (> 70 samples) using two analytical techniques: laser direct infrared (LDIR) and optical microscopy (OM) covering a size range of 0.02 to 5 mm. Comparison of the two analytical strategies shows similar trends, fluctuations, and correlating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…While this method provides valuable information and cost effective, it is time-consuming, and limited to larger MPs. This method is not suitable for smaller particles (<50 μm) (Bäuerlein et al, 2023). Several modified spectroscopic techniques are employed for its detection and quantification.…”
Section: Human Health Concerns and Implicationsmentioning
confidence: 99%
“…While this method provides valuable information and cost effective, it is time-consuming, and limited to larger MPs. This method is not suitable for smaller particles (<50 μm) (Bäuerlein et al, 2023). Several modified spectroscopic techniques are employed for its detection and quantification.…”
Section: Human Health Concerns and Implicationsmentioning
confidence: 99%
“…Microplastic particle counts were estimated initially using a fluorescent staining and automated imaging approach. Confocal microscopy was performed by scanning filters (or portions thereof) using excitation: 487 nm and emission: 525 nm for Nile Red and (only for the HSE samples -see below) excitation: 409 and emission: 450 nm for DAPI using a Nikon A1R HD according to standard methods described by [10,49,54,56,58] . Depending on the number of particles, either whole, half, or one-quarter of each filter was scanned and the images stitched together to create a composite.…”
Section: Water Column Mp (Gbe)mentioning
confidence: 99%
“…Therefore, reliable methods for identifying polymers and microplastics are needed. Methods describing how to detect nano- and microplastics in the environment include Fourier transform infrared (FTIR) spectroscopy, , Raman spectroscopy, , laser-directed infrared (LDIR) spectroscopy, ,, and thermogravimetric analysis (TGA)/pyrolysis. , Comprehensive reviews can be found in refs and . With spectroscopic methods, polymers are identified mostly through comparison with reference spectra from existing libraries.…”
Section: Introductionmentioning
confidence: 99%